2000
DOI: 10.1055/s-0037-1613821
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the R2 FV Gene Affect the Ratio between the Two FV Isoforms in Plasma

Abstract: SummaryMolecular genetics and biochemical studies were performed in homozygotes for the R2 allele (4070G) in the factor V gene, most of them affected by coronary artery disease. Novel polymorphisms (G642T, 156Ser; T1328C, 385Met/Thr), among which a functional candidate (A6755G, 2194Asp/Gly) located in the C2 domain of FV, were identified in the R2 gene. In chromatographic studies R2 FV appeared qualitatively identical to normal FV. However, a relative increase of the more thrombogenic and more glycosylated FV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 13 publications
2
66
2
2
Order By: Relevance
“…Thus, because of the absence of normal factor V in the patient's plasma, the factor V molecules resistant to APC inactivation are characterized by the mutations included in the HR2 haplotype. 7 These findings suggest the possibility that 1 or more of the amino acid substitutions predicted by the HR2 haplotype might impair factor Va cleavage at Arg506/ Arg306, possibly by preventing optimal interaction with APC. Alternatively, impaired factor Va inactivation may result from suboptimal interaction with phospholipid membranes.…”
Section: To the Editormentioning
confidence: 88%
“…Thus, because of the absence of normal factor V in the patient's plasma, the factor V molecules resistant to APC inactivation are characterized by the mutations included in the HR2 haplotype. 7 These findings suggest the possibility that 1 or more of the amino acid substitutions predicted by the HR2 haplotype might impair factor Va cleavage at Arg506/ Arg306, possibly by preventing optimal interaction with APC. Alternatively, impaired factor Va inactivation may result from suboptimal interaction with phospholipid membranes.…”
Section: To the Editormentioning
confidence: 88%
“…143 This mutation (in the B region) is a marker that cosegregates with several other polymorphisms encoding several amino acid changes in the factor V molecule. [143][144][145][146] It has been reported that individuals carrying the factor V His1299Arg mutation have mild APC resistance and an increase in the risk of venous thrombosis. Thus, this ensemble of polymorphisms represents per se a potential thrombotic risk factor.…”
Section: Defects In the Inactivation Of Factor V/va Associated With Tmentioning
confidence: 99%
“…Later on, R2 polymorphism was found to be in tight association with at least 12 polymorphisms in the factor V gene. Therefore, these SNPs were collectively called HR2 (Haplotype R2) Castoldi et al, 2000). Several studies in different parts of the world gave the prevalence of HR2 to be 9.5%-15.2% in VTE cases and 5.8%-10.4% in healthy controls, with an increased risk by at least 2.5-fold Alhenc-Gelas et al, 1999;Castoldi et al, 2000;Pecheniuk et al, 2001;Margaglione et al, 2002;Castaman et al, 2003;Faioni et al, 2004;Jadaon & Dashti, 2005a).…”
Section: Hr2 Haplotypementioning
confidence: 99%
“…The exact mechanism by which HR2 haplotype increases the risk for development of VTE is still not that clear. However, Castoldi et al (2000) have studied the two isoforms of factor V, V1 and V2, in cases with or without HR2. V1 is 7-fold more thrombogenic than V2.…”
Section: Hr2 Haplotypementioning
confidence: 99%